A taxonomy of hospitals based on partnerships for population health management. Issue 4 (October 2020) - Noh, Eunjeong; Potthoff, Sandra; Begun, James W.
Abstract : Background: Hospitals face growing pressures and opportunities to engage with partner organizations in efforts to improve population health at the community level. Variation has been observed in the degree to which hospitals develop such partnerships. Purpose: The aim of this study was to generate a taxonomy of hospitals based on their partnerships with external organizations, employing the theoretical notion of organizations' focus on exploration versus exploitation. Methodology: With 1, 238 valid cases from the 2015 American Hospital Association Population Health Survey, our study uses items asking about the level of partnership strength for 36 named partner types. Excluding three variables with low reliability, 33 variables are classified into six partner groups by factor analysis. Then, cluster analysis is conducted to generate a taxonomy of hospitals based on their partnerships with the six partner groups. Findings: Of 1, 238 hospitals, 26.1% are classified as exploratory hospitals that develop more collaborative relationships with partners outside the medical sector. Exploitative hospitals (18.3%) focus on relationships with traditional medical sector partners. Ambidextrous hospitals (27.0%) develop partnerships both in and outside the medical sector. Finally, independent hospitals (28.6%) do not establish strong partnerships. Larger hospitals, not-for-profit hospitals, and teaching hospitals are more likely to be classified as exploratory. Practice Implications: The four-cluster taxonomy can provide hospital and health system leaders and managers with a better understanding of the wide variation in partnerships that hospitals establish and insights into their different strategic options with regard to partnership development.